The outer influences the inner: Postharvest UV-B irradiation modulates peach flesh metabolome although shielded by the skin. (15th February 2021) - Santin, Marco; Ranieri, Annamaria; Hauser, Marie-Theres; Miras-Moreno, Begoña; Rocchetti, Gabriele; Lucini, Luigi; Strid, Åke; Castagna, Antonella
Highlights: Peach flesh metabolome is strongly influenced by UV-B exposure. Phenolics, terpenoids and phytoalexins highly responded to UV-B. Decreased levels of most metabolic classes were detected after 24 h. Accumulation of most metabolic classes was observed after 36 h. UV-B radiation does not penetrate peach skin. Abstract: UV-B-driven modulation of secondary metabolism in peach fruit by enhancing the biosynthesis of specific phenolic subclasses, is attracting interest among consumers. However, current literature explored the UV-B-induced metabolic changes only in peach skin subjected to direct UV-B irradiation. Accordingly, this study aimed to understand whether UV-B radiation penetrates the fruit skin and is able to induce metabolic changes also within the inner flesh. Peaches were UV-B-irradiated either 10 or 60 min, and the flesh was sampled after 24 and 36 h. Non-targeted metabolomics revealed that UV-B has a strong impact on peach flesh metabolome, determining an initial decrease after 24 h, followed by an overall increase after 36 h, particularly for terpenoids, phenylpropanoids, phytoalexins and fatty acids in the 60 min UV-B-treated samples (+150.02, +99.14, +43.79 and +25.44 log2 FC, respectively). Transmittance analysis indicated that UV-B radiation does not penetrate below the skin, suggesting a possible signalling pathway between tissues.